US gender- and sexuality-related asylum law: The politics of transgender asylum. Issue 2 (June 2016) - McKinnon, Sara L.
This essay addresses the politics undergirding the incorporation of transgender refugee provisions in the US system of political asylum. I first outline how asylum provisions for trans persons have developed through legal decisions in relation to two related categories of asylum law—gender-based asylum and sexuality-related asylum. I then question the future of transgender asylum in the context of US transnational aspirations and anxieties. What does the incorporation of particular trans asylum seekers enable? What does it conceal? What US geopolitical and economic motivations help us make sense of trans asylum? This essay serves as both a meditation on the history of trans incorporation in this institution as well as a forecasting of the future for gender-related, sexuality-related, and transgender asylum in the United States.